Developmental delay and assessment in an infant with PCWH syndrome: A case report - Ashna Kumar; Michelle do Rosario; Shahyan Siddiqui; Divyani Garg; Anju Shukla; Suvasini Sharma (Annals of Movement Disorders, 2023)
Peripheral demyelinating polyneuropathy, central dysmyelination, Waardenburg syndrome, and Hirschsprung’s disease is a rare genetic disorder caused by de novo variants in the SOX10 gene. The SOX10 gene is expressed in the neural crest cells during early embryonic development and in the glial cells of the peripheral and central nervous systems during late embryonic development, as well as in adults. Here, we describe our findings in a 9-month-old male infant presenting with failure to thrive, global developmental delay, seizures, hypotonia, heterochromia iridis, hypopigmented skin macules, pendular nystagmus, Hirschsprung’s disease, and hearing impairment. Nerve conduction studies were suggestive of sensorimotor demyelinating polyneuropathy. Brain magnetic resonance imaging showed diffuse hypomyelination. Targeted genetic testing revealed a novel stop-loss variant in the SOX10 gene (NM_006941.4). This case highlights the importance of clinical phenotyping that can aid in targeted genetic testing.